Norms for the International Outcome Inventory for Hearing Aids - Cox, Robyn M.; Alexander, Genevieve C.; Beyer, Cynthia M. (Journal of the American Academy of Audiology, 2003)
The International Outcome Inventory for Hearing Aids (IOI-HA) is a seven-item survey that was developed for use in research settings to facilitate comparison of data across diverse investigations. The inventory also has potential applications in clinical evaluation of hearing aid fitting outcomes. This article reports the development of norms for the inventory that are suitable for use with group data in research applications, and individual data in a clinical setting. The normative group was defined as adults fitted bilaterally with analog, single-channel, single-memory, compression processing, in-the-ear hearing aids. There were 154 subjects. Associations between outcomes and demographic variables (e.g., gender, hearing loss, etc.) were explored, and several relationships were seen. Based on these data, two sets of norms were derived. The appropriate set will depend on the individual's reported subjective hearing problems without amplification.
Keywords: Hearing aid; hearing loss; older adult; outcomes assessment